UNDERSTANDING AND MANAGING LONELINESS IN OLD AGE: MULTI-METHOD PERSPECTIVES. (11th November 2018) - Fang, Y; Fung, H H
Abstract: Loneliness is a serious threat to mental and physical health for older people around the globe; it is also a multifaceted phenomenon. Using varied methodological approaches and sampling from North America, Europe, and Asia, the papers in this symposium examine the circumstances that give rise to loneliness in old age, the implications of loneliness for psychological wellbeing, and the interventions for reducing loneliness among older adults. In the first paper, Wong and colleagues presented qualitative and quantitative evidence to illuminate the experience and mechanisms of loneliness among older adults at both personal and societal levels. The next two papers used ecological momentary assessments to study older adults' loneliness experience in everyday life: Lay and colleagues found that whether older adults in solitude feel lonely (or not) is shaped by different social contexts (i.e., acculturation, desire for and time in solitude); Chu and colleagues examined the emotional and motivational consequences of loneliness in younger and older adults. In the fourth paper, Tsang and colleagues followed a lifespan sample over two years and found that the fear of loneliness, often overlooked in favor of loneliness itself, explained why dissatisfying relationships are often psychologically troubling. The fifth and last paper by Fang and colleagues discussed a new intervention and its effectiveness for reducing loneliness in older adults by appealing to their need for meaning. Using diverse methodologies, these papers considered the many facets of loneliness in old age and discuss the implications for both research and practice.